Complete female epispadias with urinary incontinence: A single-stage perineal urethroplasty and cystoscopic-guided bladder neck plication - Rajat Piplani; Enono Yhoshu (Wolters Kluwer Medknow Publications, 2023)
Isolated female epispadias without bladder exstrophy is an extremely rare congenital anomaly. The presenting features of female epispadias are urinary incontinence and abnormal anatomical features. A 4-month-old girl presented with primary urinary incontinence since birth. On physical examination, she had a bifid clitoris and labia minora along with an anteriorly placed introitus and wide-open bladder neck. The vagina and hymen were normal. With the diagnosis of isolated complete female epispadias, a single-stage reconstruction of the urethra, labia minora and clitoris was performed along with cystoscopic-guided bladder neck plication. This index case highlights the surgical technique and the necessity to operate on these patients at a younger age in infancy with a single-stage perineal repair to achieve better functional and cosmetic outcomes.